Heteroleptic copper(i) complexes bearing functionalized 1H-pyrazole-bipyridine ligands: synthesis, photophysical properties, crystal structures, and applications in halogen sensing. (3rd February 2023) - Tong, Jin; Zhao, Li-Rong; Zhang, Jin; Wang, Xia-Yan; Yu, Yan-Min; Yu, Shu-Yan
Abstract : Supramolecular Cu(i ) complexes are synthesized from 2, 2′-bipyridine derivatives containing anion binding 1 H -pyrazole and their applications in halogen sensing are studied. Abstract : A series of new heteroleptic copper(i ) complexes [Cu(N^N)(P ^P )][BF4 ] (1–6 ), where N^N is a pyrazole-substituted 2, 2′-bipyridine (5-(1 H -pyrazol-4-yl)-2, 2′-bipyridine (5-pzbpy, L 1 ), 4, 4′-di(1 H -pyrazol-4-yl)-2, 2′-bipyridine (4, 4′-pz2 bpy, L 2 ), 5, 5′-di(1 H -pyrazol-4-yl)-2, 2′-bipyridine (5, 5′-pz2 bpy, L 3 ), and 3, 8-di(1 H -pyrazol-4-yl)-1, 10-phenanthroline (3, 8-pz2 phen, L 4 )) and P ^P is either oxybis(2, 1-phenylene)bis(diphenylphosphane) (POP ) or 1, 3-bis(diphenylphosphanyl)propane (dppp ), were successfully prepared and investigated. The crystal structures of 1, 2, 3 and 6 were determined by single X-ray diffraction. The novel copper(i ) complexes 1, 2 and 3 show turn-on emission sensing for halogen ions. The fluorescence enhancement of the copper(i ) complexes increases in the order of F − < I − < Br − < Cl −, and the differences in fluorescence intensity could be easily distinguished with the naked eye under UV light illumination. The 1 H NMR titration indicated that the interaction involves hydrogen-bond formation between the halide (Cl −, Br − and I − ) and the acidic H of the pyrazole group, with N–H deprotonation occurring at increasing F − concentrations. The result was further confirmed by carrying out theoretical calculations.